FINANCING BUDGET DEFICIT BY CENTRAL BANK - Kakhramonova Khusnora (Western European Studies, 2024)
The paper It is shown that conventional concept of monetary seigniorage does not reflect government gains from money creation in transitional economies. The study also reveals sources of fiscal seigniorage in the period of macroeconomic stabilization accompanied by tight monetary policy. In particular,contrary to the common view, the analysis shows that typically revenues from the money creation has not been extensively used as a tool for financing government expenditures in non of the analyzed transitional economies. Nevertheless, the research shows that in CIS countries the flow of the resources from the central bank to the budget remains significant mainly due to the reduction of the portfolio of non-government debt and quasifiscal operations of central banks.
Keywords: Deficit financing; Political and market reforms; fiscal seigniorage revenues